If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9w + -18w + -18w + 36 = 0 Reorder the terms: 36 + 9w + -18w + -18w = 0 Combine like terms: 9w + -18w = -9w 36 + -9w + -18w = 0 Combine like terms: -9w + -18w = -27w 36 + -27w = 0 Solving 36 + -27w = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + -27w = 0 + -36 Combine like terms: 36 + -36 = 0 0 + -27w = 0 + -36 -27w = 0 + -36 Combine like terms: 0 + -36 = -36 -27w = -36 Divide each side by '-27'. w = 1.333333333 Simplifying w = 1.333333333
| =6+6(x+4)+15y+x | | -1(x+4)+5=4x+1-5x | | 14+4x+6=8x | | -19x+23y=-3 | | 3x+14x+2=19 | | -4p+15=-15 | | =5(x+3)+3(y+1) | | 5x-3(x-4)=-5+4x+13 | | (x+8)(x-7)=16 | | 0=-16t^2+20t+40 | | -4w-4= | | 99-4s-6s=-9 | | 9=b | | y=xcos(x) | | 2+2=8b | | 2x-5(x-5)=-4+3x+17 | | =2(x+y)+9x+6y | | 42=3(2-6h) | | z+8(z-4)=-4 | | 2x^2-9x-12=0 | | 77-7x=11x+19 | | 6x=24+3x | | B=58b | | 3(m+5)=39 | | S=6-3 | | c-80=36 | | X=38-(-x) | | 3(x+4)-(x+5)=x+4 | | =7+4(x+5) | | f=6q-4 | | -23b=35b | | .23x+.45=8-.32x |